Determinants of a Digital Divide in Sub-Saharan Africa : A Spatial Econometric Analysis of Cell Phone Coverage - Buys, Piet; Dasgupta, Susmita; Thomas, Timothy S.; Wheeler, David (2012)
This paper investigates the determinants of disparities in coverage by cell telephone systems in Sub-Saharan Africa. It uses a spatially disaggregated probit for over 990,000 grid cells with adjustments for spatial autocorrelation. Determinants include potential market size (population); cost factors related to accessibility (elevation, slope, distance from a main road, and distance from the nearest large city); and competition policy. Estimates indicate significant results for the supply-demand variables, and very strong results for the competition policy index. Simulations suggest that a generalized improvement in competition policy could lead to huge improvements in cell phone area coverage, and to an overall coverage increase of nearly 100%.